2019
DOI: 10.3857/roj.2019.00283
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-modulated radiotherapy for stage I glottic cancer: a short-term outcomes compared with three-dimensional conformal radiotherapy

Abstract: To investigate the differences in treatment outcomes between two radiation techniques, intensity-modulated radiotherapy (IMRT) and three-dimensional conformal radiotherapy (3DCRT). Materials and Methods: We retrospectively analyzed 160 (IMRT = 23, 3DCRT = 137) patients with stage I glottic cancer treated from January 2005 through December 2016. The IMRT was performed with TomoTherapy (16 patients), volumetric-modulated arc therapy (6 patients), and step-and-shoot technique (1 patient), respectively. The 3DCRT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…In contrast to this analysis, existing retrospective data suggests similar disease control outcomes between 3D-CRT and IMRT, with potentially less toxicity with IMRT; however, these are all single-institution studies. [14][15][16] This study supports a recent publication using the National Cancer Database (NCDB) to compare 3D-CRT to IMRT for early stage glottic cancer, which found no difference in OS. 17 However, due to the limitations of the NCDB, the authors were unable to comment on CSS.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast to this analysis, existing retrospective data suggests similar disease control outcomes between 3D-CRT and IMRT, with potentially less toxicity with IMRT; however, these are all single-institution studies. [14][15][16] This study supports a recent publication using the National Cancer Database (NCDB) to compare 3D-CRT to IMRT for early stage glottic cancer, which found no difference in OS. 17 However, due to the limitations of the NCDB, the authors were unable to comment on CSS.…”
Section: Discussionsupporting
confidence: 82%
“…In view of these previous reports, efforts shall be made to keep the dose to the carotid artery to a minimum as much as possible. Many investigators have reported that IMRT techniques significantly reduce unnecessary radiation to the carotid arteries [ 6 21 ]. Although PT is another promising technology, few previously published studies have explored PT for early-stage glottic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Consideration of advanced RT technologies with minimal impact to surrounding normal tissues is worthwhile in such cases. There are many reports on IMRT for early-stage glottic cancer [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], but no reports have yet detailed the dose distribution characteristics of PT for early-stage glottic cancer. In this study, we therefore aimed to clarify the dose distribution between IMRT and PT for early-stage glottic cancer and examined the usefulness of PT for early-stage glottic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…There was a trend for increased local recurrences in the T2 N0 population, which highlighted the potential consequences for not adequately appreciating the risk of local subclinical spread above or below the glottis. Although follow-up periods are short, the dosimetric advantages to OARs and comparable local control rates for IMRT and VMAT have been further demonstrated by numerous retrospective analyses (11,(103)(104)(105)(106)(107).…”
Section: Radiotherapy Technique and Outcomesmentioning
confidence: 99%